Development of a Creativity-Based Cognitive Test Design to Measure Students' Problem-Solving Abilities (International Journal of Active Learning, 2023)
Education is a form of business that is carried out in a planned and systematic manner that aims to provide insight, knowledge, skills, and expertise to students (Kurniawan, 2015). Education is needed as a means to shape one's character and character in order to be able to face the current developments of the times, advance the nation, and be able to compete with other nations. The success of education in an area is determined by an assessment. Assessment activities carried out by a teacher cannot be separated from the use of instruments. The instrument is a measuring tool that is used to obtain information data on a matter. The use of the right assessment instrument if used will produce accurate data and assessment conclusions. So that with the accuracy of the assessment instrument, it is an important step to assist the government in the education sector. In the 2013 curriculum the assessment includes three main components, namely the assessment of knowledge, skills and attitudes which must be met in a balanced manner. Based on the results of research and discussion of test instruments to measure problem-solving abilities based on creative thinking on basic chemical laws, it can be concluded that: 1) The design of test instruments to measure problem-solving abilities based on students' creative thinking based on aspects of Fluency, Flexibility, Originality, and Elaboration, 2) The test instrument for measuring problem-solving skills based on creative thinking on the basic chemical laws material that has been developed meets valid and reliable criteria, 3) The practicality of the higher-order thinking enrichment test instrument was measured using the student and teacher response scales. The results of the responses of students and teachers stated that the response agreed to the use of test instruments to measure problem solving abilities based on students' creative thinking. These results state that the test instrument for measuring problem-solving skills based on students' creative thinking is practically used as an assessment instrument in the learning process.